Kegiatan Posyandu Penyakit Tidak Menular (PTM) – DM terhadap Kepatuhan Pengelolaan DM di Rumah pada Penyandang DM Tipe II - Rosa Delima Ekwantini; Harmilah Harmilah (POLTEKKES KEMENKES YOGYAKARTA, 2016)
WHO estimates that global prevalence of type II diabetes will increase from 171 million in 2000 to 366 million in 2030, and Indonesia was ranked fourth (Soegondo , 2007) . According to records at the health center Gamping II that the number of people with diabetes in the working area in 2014 there were about 400 people , average visit of 106 people for blood sugar control with most of the blood sugar levels while above normal ( > 200 mg / dl ) . Government efforts thathave been made to combat the disease is to provide services at the hospital level and community health centers. Services close to the people is needed to sensitize them to conduct disease management at home as well so that complications can be delayed or prevented . The aim of this study was to determine the effect of Posyandu PTM - DM compliance diabetes management at home with the type II diabetes patient.This study was a quasi experimental design with pre test - posttest design with control group The number of samples in this study were 64 respondents were divided into two group 32 respondents as a treatment group and 32 respondents as a comparison group . Consecutive sampling is used as technic sampling. Analysis of data using Mc Nemar and Chi square test . In the treatment group, compliance management of diabetes at home before the activity at Posyandu PTM - DM obedient and after activity obedient were 18 respondents , before the activities at Posyandu PTM - DM obedient and activity at Posyandu PTM - DM not obedient were 2 respondents , before and after the activity at Posyandu PTM - DM is not obedient were 10 respondents , before activity at Posyandu PTM – DM not obedient and after activities obedient were 2 respondents. Mc Nemar test results ? 0.039 ( p < 0.05) . Respondents with compliance management of diabetes at home after PTM - DM Posyandu activities adhere to the treatment group there were 28 respondents and a comparison group of 20 respondents . Respondents with compliance after Posyandu activities PTM - DM does not adhere to the treatment group there were 4 respondents , 12 respondents comparison group . Chi square test results ? 0.021 ( p < 0.05 ).Posyandu PTM - DM affect the compliance of diabetes management at home in the type II diabetes patient.